EVOLUTION AND ASSESSMENT OF LAHORE’S TEMPORAL AND SPATIAL EXPANSION FROM 1900-2015 AND PREDICT SPATIAL EXPANSION FOR NEXT 100 YEARS - Shah Nawaz (Spectrum of Engineering Sciences, 2025)
Population is the main focus in all studies within the framework of geography. Population and basic natural resources are intimately related to each other. With the increase in population the land use conflicts, traffic congestion, environmental degradation, pollution and water degradation occurs. Therefore, the study and analysis of population growth and distribution in the urban development is the logical starting point for any research of the present nature. Lahore is the second most populated city after Karachi in Pakistan. As Lahore is better developed than other cities, people from all over Punjab are moving to Lahore in strive for better employment, education, health and in general a better life style opportunities. The environment of Lahore is badly affected by increase in population and limited resources. The study of spatial temporal expansion of Lahore is carried out by gathering data of Lahore from different institutes and departments of Pakistan like Jinnah Library, Survey of Pakistan, Walled City, Lahore Development Authority (LDA) etc. This has helped in understanding of the rate at which civil infrastructure is developed in the city over the years. This study has also helped in finding the solution to control this unchecked expansion. According to research the total population of Lahore was 6,318,745 as per 1998 Census but now it has increased to ridiculous figure of 11,738,186 and it is continuously increasing. The total area of Lahore is 1772 square kilometers which was 850 square kilometers in 1998. If this unchecked expansion continues then the expected increase of population and area would be 50 million and 3000 square kilometers respectively in next 100 years. This unchecked expansion should be controlled in order to improve the living standards and environmental conditions of the millions of people living in the city of Lahore by systematic monitoring of the urban development, proper management of the City and planned future development. Development authorities are established in Pakistan's big cities to cope with this haphazard spatial growth issue. It was assigned to the Lahore Development Authority (LDA) to monitor the uneven development within city boundaries.